KERJA SAMA PT L'OREAL DENGAN KEMENTERIAN PENDIDIKAN, KEBUDAYAAN, RISET, DAN TEKNOLOGI (KEMDIKBUD) DALAM PENGEMBANGAN SUMBER DAYA MANUSIA BIDANG TATA KECANTIKAN TAHUN 2017-2022 - Vidha Ariani (2023)
This study aims to discuss the implementation of the cooperation between the Ministry of Education as a state actor and PT L'Oreal as a non-state actor in developing human resources in the field of hairstyling from 2017 to 2022 by using the concept of international cooperation, CSR by MNC, and transfer of knowledge. The method used in this research is descriptive qualitative using primary and secondary data sources. Data analysis techniques were carried out on the results of interviews and literature studies in the form of books, journal articles, website articles, and institutional official reports. It can be concluded in this study that the cooperation between the two parties provides significant benefits in the effort to develop human resources in the field of hairstyling, especially vocational high school graduates. Not only as an effort to develop human resources for hairstyling, but this collaboration can create a link and match between the world of education and the world of industry so as to create a skilled workforce with high absorption because they are suitable with the industrial needs.